HLA-DRB1 polymorphism determines susceptibility to autoimmune thyroiditis in transgenic mice: definitive association with HLA-DRB1*0301 (DR3) gene. - Kong, Yi-chi M.; Lomo, Lesley C.; Motte, Reinhard W.; Giraldo, Alvaro A.; Baisch, Jean; Strauß, Gudrun; Hämmerling, Günter J.; David, Chella S. (Journal of experimental medicine, 1996)
Familial clustering of autoimmune thyroid diseases has led to studies of their association with human major histocompatibility complex (MHC) class II genes. One such gene implicated in Hashimoto's thyroiditis (HT) is HLA-DR3, but the association is weak and is contradicted by other reports. On the other hand, murine experimental autoimmune thyroiditis (EAT), a model for HT, presents a clear linkage with MHC class II. Moreover, it is inducible with thyroglobulin (Tg), the common autoantigen in either species. Immunization of HLA-DRB1* 0301 (DR3) transgenic mice with mouse or human Tg resulted in severe thyroiditis. In contrast, transgenic mice expressing the HLA-DRB1*1502 (DR2) gene were resistant to EAT. Our studies show that HLA-DRB1 polymorphism determines susceptibility to autoimmune thyroiditis and implicate Tg as an important autoantigen.